Detection of Epstein-Barr virus DNA by polymerase chain reaction in surgical specimens of patients with squamous cell carcinoma of the larynx and vocal cord nodules. - Gök, Uzeyir; Ozdarendeli, Aykut; Keleş, Erol; Bulut, Yasemin; Cobanoglu, Bengü (My University, 2003)
OBJECTIVES: We investigated the incidence of Epstein-Barr virus (EBV) infection in surgical specimens of squamous cell carcinoma of the larynx and vocal cord nodules. PATIENTS AND METHODS: Formalin-fixed, paraffin-embedded tissue samples randomly selected from 22 patients with squamous cell carcinoma of the larynx (20 males, 2 females; mean age 52 years) and from 17 patients with vocal cord nodules (14 males, 3 females; mean age 38 years) were examined by the polymerase chain reaction. The patients were assessed in terms of localization of the disease, smoking habits, duration of smoking, and the presence or absence of EBV DNA. RESULTS: Twenty-one patients with laryngeal carcinoma and nine patients with vocal cord nodules were smokers. Polymerase chain reaction showed EBV DNA in 11 patients (50%) with laryngeal carcinoma and in seven patients (41.2%) with vocal cord nodules. No significant differences were found with respect to EBV DNA positivity, smoking habits, smoking period, the number of cigarettes consumed daily, localization of disease, and tumor stage (p>0.05). CONCLUSION: Epstein-Barr virus does not seem to be directly associated with the pathogenesis of laryngeal squamous cell carcinoma, but its role in the etiology of laryngeal proliferative diseases needs more elucidation.
Keywords: Carcinoma, Squamous Cell; DNA Primers; DNA, Viral; Female; Herpesvirus 4, Human; Humans; Incidence; Laryngeal Neoplasms; Male; Middle Aged; Paraffin Embedding; Polymerase Chain Reaction; Smoking; Turkey; paraffin; primer DNA; virus DNA; article; Epstein Barr virus; female; genetics; human; incidence; isolation and purification; larynx tumor; male; middle aged; polymerase chain reaction; smoking; squamous cell carcinoma; Turkey (republic); virology